Assessing the Long-Run Effects of Institutional Distortions, Economic Growth, and Labor Participation on Educated Unemployment: An Islamic Economics Perspective - Chairani Firstia Rizal; Marina Oktari; Aryadimas Suprayitno; Sulistya Rusgianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Educated unemployment remains one of the most critical challenges in Indonesia, reflecting a persistent mismatch between the education system and labor market demand. Despite continuous economic growth, the absorption of educated labor remains limited, indicating structural problems in employment creation. This study aims to analyze educated unemployment in Indonesia by examining the roles of economic growth, institutional distortions, and labor force participation in both the short run and the long run. The study employs a quantitative approach using a Vector Error Correction Model (VECM) based on annual time-series data from 1986 to 2024. Data are obtained from Statistics Indonesia (BPS), the World Bank, and Transparency International. The results indicate the existence of a long-run cointegrating relationship among the variables. Economic growth is positively associated with educated unemployment in the long run, suggesting jobless growth and limited creation of high-skilled jobs. Institutional distortions, reflected in weak governance and non-merit-based recruitment, persistently worsen employment outcomes for graduates. Increases in labor force participation further intensify competition when job creation does not keep pace. The findings suggest that reducing educated unemployment in Indonesia requires inclusive growth, stronger institutional governance, and better alignment between education and labor market needs. Policy efforts should also promote entrepreneurship and productive employment through Islamic social finance instruments to support sustainable job creation for educated workers.